High-activity hydrodemetallization catalyst and preparation method thereof

By forming a carbon film and a macroporous structure of silicon carbide nanoparticles on the catalyst surface, the problems of low demetallization rate and insufficient stability of the catalyst in residue oil hydrotreating are solved, and high activity and long-cycle operation of the catalyst are achieved.

CN120733768AActive Publication Date: 2025-10-03SHANDONG GAODE LUTIAN CATALYST CO LTD
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202511189102.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-08-25
Publication Date
2025-10-03
Estimated Expiration
2045-08-25

AI Technical Summary

Technical Problem

The existing catalysts have a low demetallization rate in fixed-bed residue oil hydrotreating, and the surface active site stability and anti-carbon deposition ability are insufficient, resulting in a short operating cycle of the device and difficulty in meeting long-term operation requirements.

Method used

A modified catalyst body and covering layer structure is adopted, and a carbon film layer is covered on the outer surface of the catalyst. Silicon carbide nanoparticles are dispersed in the carbon film to form a macroporous structure. The anti-carbon deposition performance is improved through the COP bonding network and Si-OC covalent bonds, and high-temperature cracking is avoided through gradient buffering, thereby enhancing mechanical stability.

Benefits of technology

The demetallization rate and stability of the catalyst are improved, the operation cycle of the device is extended, high activity is maintained, and the carbon deposition and thermal cracking risks are reduced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The invention discloses a high-activity hydrodemetallization catalyst and a preparation method thereof, and belongs to the field of hydrogenation catalysts.The catalyst comprises a modified catalyst body composed of a carrier, an active component modifier and an additive, and a carbon film layer covering the outer surface of the modified catalyst body, silicon carbide nanoparticles are dispersed in the carbon film, and the silicon carbide nanoparticles account for 5-15% of the mass of the carbon film; the carbon film layer covers a surface active center, inhibits severe reaction of residual oil at an active site, effectively prevents carbon deposit, sulfide and metal deposits from blocking pore channels and covering the active site, and improves carbon deposit resistance and catalyst stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of hydrogenation catalysts, and in particular relates to a high-activity hydrogenation demetallization catalyst and a preparation method thereof. Background Art

[0002] In the petrochemical and fine chemical industries, hydrodemetallization (HDM) technology is widely used to produce high-quality products and remove harmful impurities from catalysts. Fixed-bed residue hydrotreating technology is an effective means of achieving efficient conversion of heavy oils. However, due to the complex composition of residue oil, it is not only rich in metal impurities at hundreds of ppm levels but also contains large amounts of macromolecules such as colloids and asphaltenes. Its hydrogenation reaction is accompanied by multiple risks of irreversible deactivation. Effective catalytic removal of impurities such as metals, sulfur, nitrogen, and carbon residue from the residue is required. A single catalyst is insufficient for this task, and a matching loading system with catalysts of varying functions, shapes, and sizes is required to achieve high activity and long-term operation. Residue hydrotreating catalysts typically include protective catalysts, demetallization catalysts, desulfurization catalysts, and denitrification catalysts, each of which performs other functions. The HDM catalyst removes metals such as Ni and V from the residue oil while also protecting the desulfurization catalyst. It not only removes metal impurities from the feed but also must accommodate as much of these metals and impurities as possible, including coke.

[0003] Fixed-bed residue hydrotreating technology is mature, but due to carbon and metal deposition in the catalyst, the operating cycle of fixed-bed residue hydrotreating units is significantly shortened (approximately 12 months), far shorter than the 2-3 year cycles of upstream and downstream units such as atmospheric and vacuum distillation and catalytic cracking. This forces refineries to frequently shut down for catalyst replacement, severely restricting the economic and continuity of efficient conversion of heavy, low-quality crude oil. Therefore, the operating cycle of fixed-bed residue hydrotreating units has a significant impact on the overall operation and economic benefits of the refinery. Although traditional hydrodemetallization (HDM) catalysts delay deactivation by optimizing the support pore structure, they still have significant drawbacks. For example, the thin alumina layer easily shrinks, cracks, and even peels off under the high temperature, high pressure, and thermal cycling conditions of residue hydrotreating, losing its protective function and resulting in reduced catalyst activity. Furthermore, it is difficult to effectively control the reaction intensity of macromolecules at the active sites.

[0004] Patent CN202111277860.6 discloses a residual oil hydroprocessing catalyst and its preparation method and application. The catalyst includes alumina and a hydrogenation metal supported on alumina, and the hydrogenation metal is selected from at least one of Group VIB and / or Group VIII metals. The catalyst preparation method includes preparing alumina powder, preparing a first intermediate, and a second intermediate; finally, the second intermediate, a compound containing Group VIB, a compound of Group VIII metal, and an extrusion aid are mixed and then formed, dried, and calcined to obtain a catalyst. The catalyst of this invention does not construct a physical protective layer to actively shield the pores and surface active centers from direct attack by macromolecules and metal deposits. It relies on a dual-active phase alumina support and does not introduce a reinforcing phase with high thermal stability and high thermal conductivity into the active component. Therefore, when the catalyst is faced with high metal content and coke-prone residual oil raw materials for a long time, its ability to maintain pore duct obstruction is limited, and the catalyst activity cannot be maintained for a long time, making it difficult to meet the catalyst stability requirements for long-term operation of the device.

[0005] Therefore, there is an urgent need to develop a catalyst with a lower demetallization rate, resistance to metal deposition on the outer surface, stability of surface active sites, and overall greater stability to meet the long-term needs of the industry. Summary of the Invention

[0006] In order to solve the problems of low demetallization rate, insufficient stability of surface active sites and anti-carbon deposition ability of existing catalysts, the present invention provides a high-activity hydrodemetallization catalyst and a preparation method thereof.

[0007] The purpose of the present invention can be achieved through the following technical solutions: A high-activity hydrodemetallization catalyst comprises a modified catalyst body and a covering layer; the modified catalyst body is composed of a carrier, an active component modifier, and the active component supported on the carrier; the covering layer is a carbon film layer covering the outer surface of the modified catalyst body, and the thickness of the carbon film is 1-300 μm; silicon carbide nanoparticles are dispersed in the carbon film, and the mass of the silicon carbide nanoparticles accounts for 5-15% of the total mass of the carbon film.

[0008] Preferably, the carbon membrane has a macroporous structure with a pore volume of 1.2-1.5 cm 3 / g, with an average pore size greater than 50nm; the particle size of the silicon carbide nanoparticles is 20-100nm, and the specific surface area is greater than 80m 2 / g.

[0009] Preferably, a method for preparing a high-activity hydrodemetallization catalyst comprises the following steps: Step 1: Preparation of molybdenum nickel phosphorus solution and impregnation Prepare 100 mL of molybdenum nickel phosphorus solution, wherein the mass of MoO3 is 8-10 g, the mass of NiO is 2-2.6 g, the content of phosphorus is 1-1.4 g, and the rest is deionized water. Add active component modifier and additives to the molybdenum nickel phosphorus solution in sequence, stir at room temperature for 20-40 minutes to obtain an impregnation solution, and impregnate the alumina support with the impregnation solution. The pore volume of the support is 0.9-1.4 cm 3 / g, with a specific surface area of ​​90-130m 2 / g, to obtain an impregnated alumina support, drying the impregnated alumina support at 105-115° C. for 2-4 h, and then calcining at 520-580° C. for 3-6 h to obtain a modified catalyst body; Step 2: Surface treatment and carbonization The modified catalyst body obtained in the first step is soaked in an ammonium bicarbonate solution containing 8-12% by mass, an aqueous starch solution containing 8-15% by mass, and a silicon carbide suspension for 5-20 minutes, and then taken out. The taken out catalyst is then carbonized to obtain a high-activity hydrodemetallization catalyst.

[0010] Preferably, the active component modifier includes gluconic acid added in an amount of 0.01-0.05 g / mL, ammonium hydrogen phosphate added in an amount of 0.01-0.03 g / mL, and potassium nitrate added in an amount of 0.01-0.02 g / mL.

[0011] Preferably, the additive includes one or a combination of ethylene glycol, polyethylene glycol, glycerol, xanthan gum, guar gum, and polyvinyl alcohol.

[0012] Preferably, the additive is added in an amount of 0.1-0.4 g / mL.

[0013] Preferably, the method for preparing the silicon carbide suspension comprises the following steps: Silicon carbide nanoparticles are added to a 45-55wt% ethanol solution, ultrasonicated at 40-60kHz for 20-40min with an ultrasonic power of 300-500W, then sodium polyacrylate and gluconic acid are added, stirred at 40-50°C for 0.5-1h with a stirring rate of 300-400rpm, and allowed to stand for 3-5h to obtain a silicon carbide suspension.

[0014] Preferably, the mass ratio of silicon carbide nanoparticles, sodium polyacrylate and gluconic acid is 10:0.2-0.4:0.1-0.2.

[0015] Preferably, the carbonization treatment conditions are pre-oxidation at 180-250° C. for 4-12 h, and then carbonization at 350-480° C. for 4-10 h in a nitrogen atmosphere.

[0016] Beneficial effects of the present invention: 1. The high-activity hydrodemetallization catalyst obtained by the present invention is coated with a carbon film on the surface. The carbon film covers the active sites on the surface. During the pre-oxidation process, the carboxyl groups in the gluconic acid and the phosphate radicals generated by the thermal decomposition of ammonium hydrogen phosphate form a COP bonding network, which enhances the carbon film-support interface bonding strength and improves the anti-coking performance. In addition, the carboxyl groups (-COOH) and the hydroxyl groups (-OH) chelate Ni 2+ / Mo 6+ , forming a steric hindrance effect, inhibiting high-temperature migration; the phosphorus atoms of ammonium hydrogen phosphate form strong PO-Mo / Ni chemical bonds with active metals (Mo, Ni), anchoring the metal active sites, and the hydrogen phosphate generated by the decomposition of phosphate can preferentially adsorb metal porphyrin compounds, preventing them from contacting the active centers; in the present invention, an appropriate amount of potassium nitrate weakens the surface acid strength and acid amount of the catalyst, which is beneficial to reducing the amount of carbon deposits on the catalyst, and the potassium ions are embedded in the interlayer of the alumina carrier, which can inhibit the lattice shrinkage during its phase change process and improve the mechanical stability and anti-carbon deposition performance.

[0017] 2. The thermal expansion coefficient of silicon carbide in the present invention (4.5×10 -6 / ℃) between carbon layers (1.2×10 -6 / ℃) and alumina support (8.0×10 -6 / ℃), forming a gradient buffer to prevent the carbon film from cracking at high temperatures; after being embedded in the carbon film, the surface silicon dioxide forms Si-OC covalent bonds with the carbon matrix after carbonization, which improves the mechanical properties of the carbon film; the thermal conductivity of silicon carbide (120 W / m·K) promotes the diffusion of reaction heat, which can eliminate local overheating and reduce carbon deposition caused by thermal cracking. DETAILED DESCRIPTION

[0018] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the embodiments described are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making any creative efforts shall fall within the scope of protection of the present invention.

[0019] The pore volume of the catalyst in the examples was measured by mercury intrusion porosimetry, and the specific surface area was measured by nitrogen adsorption-desorption method.

[0020] Example 1: This example discloses a method for preparing a silicon carbide suspension, comprising the following steps: 20 g of silicon carbide nanoparticles were added to 200 mL of 45 wt% ethanol solution, ultrasonicated at 40 kHz for 20 min with an ultrasonic power of 300 W, then 0.4 g of sodium polyacrylate and 0.2 g of gluconic acid were added, stirred at 40 ° C for 0.5 h with a stirring rate of 300 rpm, and allowed to stand for 3 h to obtain a silicon carbide suspension.

[0021] This embodiment discloses a method for preparing a high-activity hydrodemetallization catalyst, comprising the following steps: Step 1: Preparation of molybdenum nickel phosphorus solution and impregnation Prepare 100 mL of molybdenum nickel phosphorus solution, wherein the mass of MoO3 is 8 g, the mass of NiO is 2 g, the content of phosphorus is 1 g, and the rest is deionized water. Add 1 g of gluconic acid, 1 g of ammonium hydrogen phosphate, 1 g of potassium nitrate and 10 g of glycerol to the molybdenum nickel phosphorus solution in sequence, stir at 25 ° C for 20 min to obtain an impregnation solution, and impregnate 80 g of alumina support with the impregnation solution. The pore volume of the support is 0.96 cm 3 / g, specific surface area is 122m 2 / g, to obtain an impregnated alumina support, drying the impregnated alumina support at 105 ° C for 2 h, and then calcining at 520 ° C for 3 h to obtain a modified catalyst body; Step 2: Surface treatment and carbonization The modified catalyst body obtained in the first step was soaked in an 8% by mass ammonium bicarbonate solution, an 8% by mass starch aqueous solution, and a silicon carbide suspension for 5 minutes and then taken out. The taken out catalyst was then carbonized, pre-oxidized at 180°C for 4 hours, and then carbonized at 350°C for 4 hours under a nitrogen atmosphere to obtain a high-activity hydrodemetallization catalyst A1.

[0022] Example 2: This example discloses a method for preparing a silicon carbide suspension, comprising the following steps: 20 g of silicon carbide nanoparticles were added to 200 mL of 55 wt% ethanol solution, ultrasonicated at 60 kHz for 40 min with an ultrasonic power of 500 W, then 0.8 g of sodium polyacrylate and 0.4 g of gluconic acid were added, stirred at 50 ° C for 1 h with a stirring rate of 400 rpm, and allowed to stand for 5 h to obtain a silicon carbide suspension.

[0023] This embodiment discloses a method for preparing a high-activity hydrodemetallization catalyst, comprising the following steps: Step 1: Preparation of molybdenum nickel phosphorus solution and impregnation Prepare 100 mL of molybdenum nickel phosphorus solution, wherein the mass of MoO3 is 10 g, the mass of NiO is 2.6 g, the content of phosphorus is 1.4 g, and the rest is deionized water. 5 g of gluconic acid, 3 g of ammonium hydrogen phosphate, 2 g of potassium nitrate solution and 40 g of glycerol solution are added to the molybdenum nickel phosphorus solution in sequence, and stirred at 25 ° C for 40 min to obtain an impregnation solution. The impregnation solution is used to impregnate 80 g of alumina support with a pore volume of 0.96 cm 3 / g, specific surface area is 122m 2 / g, to obtain an impregnated alumina support, drying the impregnated alumina support at 115 ° C for 4 h, and then calcining it at 580 ° C for 6 h to obtain a modified catalyst body; Step 2: Surface treatment and carbonization The modified catalyst body obtained in the first step was soaked in a solution containing 12% by mass of ammonium bicarbonate solution, 15% by mass of starch aqueous solution and silicon carbide suspension for 20 minutes and then taken out. The taken out catalyst was then carbonized, pre-oxidized at 250°C for 12 hours, and then carbonized at 480°C for 10 hours under a nitrogen atmosphere to obtain a high-activity hydrodemetallization catalyst A2.

[0024] Example 3: This example discloses a method for preparing a silicon carbide suspension, comprising the following steps: 20 g of silicon carbide nanoparticles were added to 200 mL of 50 wt% ethanol solution, ultrasonicated at 50 kHz for 30 min with an ultrasonic power of 400 W, then 0.6 g of sodium polyacrylate and 0.3 g of gluconic acid were added, stirred at 45 ° C for 0.8 h with a stirring rate of 350 rpm, and allowed to stand for 4 h to obtain a silicon carbide suspension.

[0025] This embodiment discloses a method for preparing a high-activity hydrodemetallization catalyst, comprising the following steps: Step 1: Preparation of molybdenum nickel phosphorus solution and impregnation Prepare 100 mL of molybdenum nickel phosphorus solution, wherein the mass of MoO3 is 9 g, the mass of NiO is 2.4 g, the content of phosphorus is 1.2 g, and the rest is deionized water. 3.2 g of gluconic acid, 2.4 g of ammonium hydrogen phosphate, 1.5 g of potassium nitrate and 20 g of glycerol are added to the molybdenum nickel phosphorus solution in sequence, and stirred at 25 ° C for 30 min to obtain an impregnation solution. The impregnation solution is used to impregnate an alumina support with a pore volume of 0.96 cm 3 / g, specific surface area is 122m 2 / g, to obtain an impregnated alumina support, drying the impregnated alumina support at 110°C for 3 h, and then calcining at 560°C for 5 h to obtain a modified catalyst body; Step 2: Surface treatment and carbonization The modified catalyst body obtained in the first step was soaked in a 10% by mass ammonium bicarbonate solution, a 10% by mass starch aqueous solution, and a silicon carbide suspension for 15 minutes and then taken out. The taken out catalyst was then carbonized, pre-oxidized at 200°C for 8 hours, and then carbonized at 400°C for 8 hours under a nitrogen atmosphere to obtain a high-activity hydrodemetallization catalyst A3.

[0026] Comparative Example 1 The same method as Example 3 was used, except that glycerol was not added to the molybdenum-nickel-phosphorus solution, to obtain a highly active hydrodemetallization catalyst B.

[0027] Comparative Example 2: This comparative example discloses a method for preparing a high-activity hydrodemetallization catalyst, comprising the following steps: Step 1: Preparation of molybdenum nickel phosphorus solution and impregnation Prepare 100 mL of molybdenum nickel phosphorus solution, wherein the mass of MoO3 is 9 g, the mass of NiO is 2.4 g, the content of phosphorus is 1.2 g, and the rest is deionized water. 3.2 g of gluconic acid, 2.4 g of ammonium hydrogen phosphate and 20 g of glycerol are added to the molybdenum nickel phosphorus solution in sequence, and stirred at 25 ° C for 30 min to obtain an impregnation solution. The impregnation solution is used to impregnate the alumina support. The pore volume of the support is 0.96 cm 3 / g, specific surface area is 122m 2 / g to obtain an impregnated alumina support, which was dried at 110°C for 3h and then calcined at 560°C for 5h to obtain a catalyst body.

[0028] The second step is to obtain the impregnated alumina carrier, dry the impregnated alumina carrier at 110° C. for 3 h, and then calcine at 560° C. for 5 h to obtain the catalyst body.

[0029] Step 2: Preparation of molybdenum nickel phosphorus solution and impregnation Prepare 100 mL of molybdenum nickel phosphorus solution, wherein the mass of MoO3 is 9 g, the mass of NiO is 2.4 g, the content of phosphorus is 1.2 g, and the rest is deionized water. Add 1.5 g of potassium nitrate and 20 g of glycerol to the molybdenum nickel phosphorus solution in sequence, stir at 25 ° C for 30 min to obtain an impregnation solution, and impregnate the alumina support with the impregnation solution. The pore volume of the support is 0.96 cm 3 / g, specific surface area is 122m 2 / g to obtain an impregnated alumina support, which was dried at 110°C for 3h and then calcined at 560°C for 5h to obtain a catalyst body.

[0030] Step 2: Surface treatment and carbonization The catalyst body obtained in the first step was soaked in a 10% by mass ammonium bicarbonate solution, a 10% by mass starch aqueous solution, and the silicon carbide suspension in Example 3 for 15 minutes and then taken out. The taken out catalyst was then carbonized by pre-oxidation at 200°C for 8 hours and then carbonized at 400°C for 8 hours under a nitrogen atmosphere to obtain a high-activity hydrodemetallization catalyst D.

[0031] Comparative Example 4: This comparative example discloses a method for preparing a high-activity hydrodemetallization catalyst, comprising the following steps: Step 1: Preparation of molybdenum nickel phosphorus solution and impregnation Prepare 100 mL of molybdenum nickel phosphorus solution, wherein the mass of MoO3 is 9 g, the mass of NiO is 2.4 g, the content of phosphorus is 1.2 g, and the rest is deionized water. 3.2 g of gluconic acid, 2.4 g of ammonium hydrogen phosphate, 1.5 g of potassium nitrate and 20 g of glycerol are added to the molybdenum nickel phosphorus solution in sequence, and stirred at 25 ° C for 30 min to obtain an impregnation solution. The impregnation solution is used to impregnate an alumina support with a pore volume of 0.96 cm 3 / g, specific surface area is 122m 2 / g, to obtain an impregnated alumina support, drying the impregnated alumina support at 110°C for 3 h, and then calcining at 560°C for 5 h to obtain a modified catalyst body; Step 2: Surface treatment and carbonization The modified catalyst body obtained in the first step was soaked in a 10% by mass ammonium bicarbonate solution and a 10% by mass starch aqueous solution for 15 minutes and then taken out. The taken out catalyst was then carbonized, pre-oxidized at 200°C for 8 hours, and then carbonized at 400°C for 8 hours under a nitrogen atmosphere to obtain a high-activity hydrodemetallization catalyst E.

[0032] Comparative Example 5 Prepare 100 mL of molybdenum nickel phosphorus solution, wherein the mass of MoO3 is 9 g, the mass of NiO is 2.4 g, the content of phosphorus is 1.2 g, and the rest is deionized water. Add 20 g of glycerol to the molybdenum nickel phosphorus solution and stir at 25 ° C for 30 min to obtain an impregnation solution. The impregnation solution is used to impregnate the alumina support. The pore volume of the support is 0.96 cm 3 / g, specific surface area is 122m 2 / g to obtain an impregnated alumina support, which was dried at 110°C for 3 h and then calcined at 560°C for 5 h to obtain a high-activity hydrodemetallization catalyst F.

[0033] The physicochemical properties of the high-activity hydrodemetallization catalyst are shown in Table 1: Table 1

[0034] The properties of the crude oil are listed in Table 2: Table 2

[0035] The experimental process conditions are listed in Table 3: Table 3

[0036] In a fixed-bed hydroprocessing test apparatus, the content of various impurities in the product oil was determined by the following method, and the metal removal rate was calculated: Demetallization rate (HDM, %) = (Feedstock oil metal (Ni+V) content - Product metal (Ni+V) content) / Feedstock oil metal (Ni+V) content × 100%. The demetallization rate of the high-activity hydrodemetallization catalyst was calculated. The results of the demetallization rate (%) are shown in Table 4: Table 4

[0037] It can be seen from Table 4 that, compared with Comparative Examples 1-5, the high-activity hydrodemetallization catalysts prepared in Examples 1-3 have better demetallization performance and good stability, and can maintain high activity for a long time.

[0038] It should be noted that, in this document, relational terms such as first and second, etc., are used only to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any actual relationship or order between these entities or operations. Moreover, the terms "comprises," "comprising," or any other variations thereof are intended to cover non-exclusive inclusion, such that a process, method, article, or apparatus that includes a list of elements includes not only those elements but also other elements not explicitly listed, or elements inherent to such process, method, article, or apparatus.

[0039] While embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions, and variations may be made to these embodiments without departing from the principles and spirit of the invention, and that the scope of the invention is defined by the appended claims and their equivalents.

Claims

1. A high-activity hydrodemetallization catalyst, characterized in that: It includes a modified catalyst body and a covering layer; the modified catalyst body is composed of a carrier, an active component modifier and an active component supported on the carrier; the covering layer is a carbon film layer covering the outer surface of the modified catalyst body, and the thickness of the carbon film is 1-300μm; silicon carbide nanoparticles are dispersed in the carbon film, and the mass of the silicon carbide nanoparticles accounts for 5-15% of the total mass of the carbon film.

2. The high-activity hydrodemetallization catalyst according to claim 1, characterized in that The carbon film has a macroporous structure with a pore volume of 1.2-1.5 cm³ / g and an average pore diameter greater than 50 nm; the silicon carbide nanoparticles have a particle size of 20-100 nm and a specific surface area greater than 80 m 2 / g.

3. A method for preparing a high-activity hydrodemetallization catalyst according to any one of claims 1 to 2, characterized in that: The following steps are involved: Step 1: Preparation of molybdenum nickel phosphorus solution and impregnation Prepare 100 mL of molybdenum nickel phosphorus solution, wherein the mass of MoO3 is 8-10 g, the mass of NiO is 2-2.6 g, the content of phosphorus is 1-1.4 g, and the rest is deionized water. Add active component modifier and additives to the molybdenum nickel phosphorus solution in sequence, stir at room temperature for 20-40 minutes to obtain an impregnation solution, and impregnate the alumina support with the impregnation solution. The pore volume of the support is 0.9-1.4 cm 3 / g, with a specific surface area of ​​90-130m 2 / g, to obtain an impregnated alumina support, drying the impregnated alumina support at 105-115° C. for 2-4 h, and then calcining at 520-580° C. for 3-6 h to obtain a modified catalyst body; Step 2: Surface treatment and carbonization The modified catalyst body obtained in the first step is soaked in an ammonium bicarbonate solution containing 8-12% by mass, an aqueous starch solution containing 8-15% by mass, and a silicon carbide suspension for 5-20 minutes, and then taken out. The taken out catalyst is then carbonized to obtain a high-activity hydrodemetallization catalyst.

4. The method for preparing a high-activity hydrodemetallization catalyst according to claim 3, characterized in that: The active component modifier includes gluconic acid added in an amount of 0.01-0.05 g / mL, ammonium hydrogen phosphate added in an amount of 0.01-0.03 g / mL, and potassium nitrate added in an amount of 0.01-0.02 g / mL.

5. The method for preparing a high-activity hydrodemetallization catalyst according to claim 3, characterized in that: The additives include one or a combination of ethylene glycol, polyethylene glycol, glycerol, xanthan gum, guar gum, and polyvinyl alcohol.

6. The method for preparing a high-activity hydrodemetallization catalyst according to claim 3, characterized in that: The amount of the additive added is 0.1-0.4 g / mL.

7. The method for preparing a high-activity hydrodemetallization catalyst according to claim 3, characterized in that: The method for preparing the silicon carbide suspension comprises the following steps: Silicon carbide nanoparticles are added to a 45-55wt% ethanol solution, ultrasonicated at 40-60kHz for 20-40min with an ultrasonic power of 300-500W, then sodium polyacrylate and gluconic acid are added, stirred at 40-50°C for 0.5-1h with a stirring rate of 300-400rpm, and allowed to stand for 3-5h to obtain a silicon carbide suspension.

8. The method for preparing a high-activity hydrodemetallization catalyst according to claim 3, characterized in that: The mass ratio of silicon carbide nanoparticles, sodium polyacrylate and gluconic acid is 10:0.2-0.4:0.1-0.

2.

9. The method for preparing a high-activity hydrodemetallization catalyst according to claim 3, characterized in that: The carbonization treatment conditions are: pre-oxidation at 180-250° C. for 4-12 hours, and then carbonization at 350-480° C. for 4-10 hours under a nitrogen atmosphere.

Citation Information

Patent Citations

  • A residue oil hydroprocessing catalyst and its preparation method and application

    CN116060041B

  • Pd / TiO2-C-SiC catalyst as well as preparation and application thereof

    CN103301864A

  • Method for treating catalyst

    CN107537587A

  • Residual oil hydrodemetallization catalyst and preparation method thereof

    CN114425374A

  • High-efficiency catalyst for residual oil hydrogenation and preparation method thereof

    CN116510760A